The Hemoglobin Levels and Hematocrit Decrement is less in Severe Preeclampsia Patients Undergoing Caesarean Section with B-Lynch as Prophylaxis - Parwis, Ahmad; Anwar, Anita D; Irianti, Setyorini (Indonesian Journal of Obstetrics and Gynecology, 2013)
Objective: To analyze the differences between the reduction in hemoglobin and hematocrit level in severe preeclampsia patients who have had Caesarean section with and without B-Lynch prophylaxis. Method: The design of the study was an experimental analytic with Randomized Control Trial (RCT). Thirty patients who came to Dr. Hasan Sadikin Hospital, Soreang Hospital, and Cibabat Hospital during 11 July - 25 September 2012 and met inclusion criteria were selected and divided into two groups. The first group were caesarean section with B-Lynch prophylaxis, the second one were without BLynch prophylaxis. The sample were taken with simple random sampling. Each patient were examined for hemoglobin and hematocrit level before and 6 hour after C section. The data was analyzed by t-test and Mann Whitney test. Result: There were significant differences (p <0.05) on the decrease of hemoglobin and hematocrit level between patient who were performed B-Lynch prophylaxis and those who were not (7.98% vs 19.75%; p = 0.001 and 9.02% vs 18.28%, p = 0.013, respectively). Conclusion: The decreasing hemoglobin and hematocrit level before and 6 hour after C section is less in patient with severe preeclampsia who had caesarean section with B-Lynch prophylaxis compared to cesarean section without B-Lynch prophylaxis. [Indones J Obstet Gynecol 2013; 1-3: 139-44] Keywords: B-Lynch, postpartum haemorrhage, preeclampsia